SURVEI BIBLIOGRAFIS KAJIAN PENULISAN AL-QUR’AN - Madzkur, Zaenal Arifin (SUHUF, 2019)
The academic debate related to the possibility of writing of the Qur'an using the grammatical Arabic system and that of the rasm usmani is very dynamic and has not been ended hitherto. That phenomenon is reflected in the development of the rasm usmani (the system of writing the Qur’an) literature which emerges almost in every century. This paper aims to show the richness of the Qur’anic study writing in the rasm usmani in the Islamic world. This survey traces the works of Qur’an scholars in the Islamic world from the 2nd to the 14th century Hijri whose physical evidence can be found until today. The references of the writing of the Qur’anic manuscripts come from these works. Starting from the literature which discusses the differences in writing until the time of the compilation of manuscripts, and the emergence of ash-Shaikh?n? in the 5th century Hijri. This survey shows that the richness of the study of the writing of the Qur’an using the rasm usmani is dynamic and varied. In addition to that, it shows the development and shocking differences in the form of the study of Qur’anic writing with thematic and tahl?l? patterns per verse, as well as its development which starts to lead to i?j?z in the form of writing of rasm usmani.